Terapi Kognitif Dengan Metode EFT (Emotional Freedom Technique) Pada Penyesuaian Ibu Dengan Anak Autis - Barkah Wulandari; Meidiana Dwidiyanti (Jurnal Keperawatan Notokusumo, 2016)
Background : Mothers who have children with autism always have a problem in adjustment that causes mothers stressed. The presence of children with autism in a family is certainly going to affect the lives of entire families, including the mother. There should be appropriate measures to solve the problem so that the role of mother in the family is not disturbed. Objective : The aim of this research is to conduct case studies on cognitive therapy management using EFT (Emotional Freedom Technique) in the adjustment of mothers with autistic children. Method : The study used a qualitative approach with case studies using in-depth interview, action research and observation. The study used five samples of partisipants who experienced problems of adjustment in Boyolali. Result : Psychological problems or stress in mothers with autistic children came from the lack of family support, economic problems, especially for the cost of child care and education of autism, relationships with other family members, child care difficulties and autism mothers? fears for the future of children with autism. The stress responses felt by mothers with autism children included confusion, anger, and sadness. Meanwhile, the physical response to stress was indicated by palpitations, cold sweat, heavy and dizzy head. The responses of mothers with autistic children aftercognitive therapy with EFT methods included the mother's easy smile, increased eye contact, feeling of not being alone in facing problems, feeling more spacious and quiet and normal vital signs when measured. Coclusion : Cognitive therapy with EFT to help mothers in eliminating negative emotions in the adjustment of mothers with autistic children.